Experimental analysis of models for thesauri - Balys, Vaidas (Lietuvos matematikos rinkinys, 2001)
Estimating and comparing the rate of growth of various science fields becomes very interesting and essential problem. Evolving sets of keyphrases (and keywords) observed in representative journals carry all needed information about this development. A model for the growth of thesauri as well as asymptotic properties and estimators for the parameters are proposed in [1]. The results of experimental analysis enable these properties and estimators to be used for practical calculations.The analysis suggests that sufficient accuracy of approximations is achieved quite fast – for sequences of few hundred length.Statistical analysis of ``Discrete Mathematics'' journal keyphrases database illustrate the use and the reliability of estimations.